The Influence of Career Development, Positive Psychology, Organizational Communication, and Strategic Digital Leadership on the Improvement of Performance in the Aviation School Organization of the Ministry of Transportation, Mediated by Employee Motivation - Fatonah, Feti; Arafah, Willy; Anggiani, Sarfilianty (Ridwan Institute, 2024)
This research investigates the factors influencing organizational performance within the Flight School of the Ministry of Transportation, focusing on the unique structure of the Public Service Agency (BLU) and its technical implementation units. It explores challenges faced by aviation service schools in meeting BLU revenue targets and highlights the significance of human resource management. Drawing on insights from scholars, the study examines the impact of career development, positive psychology, organizational communication, and digital leadership strategies on organizational performance, mediated by employee motivation. Using a quantitative approach involving a survey of 175 officials and Structural Equation Modeling (SEM), the research finds positive influences of these factors on organizational performance, with employee motivation playing a mediating role. However, limitations such as reliance on self-reported data and the sample size constrain the generalizability of findings. Future research could employ qualitative methods and longitudinal studies to deepen understanding and investigate long-term effects.